Comprehensive studies of aluminum drill pipe materials - Alina Ildarovna Shakirova; Rustem Adipovich Ismakov; Akhtyam Khalimovich Agliullin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the discussed issue is caused by the need to use high quality material of drilling and rock cutting tool for developing remote regions of the Far North and Arctic offshore. The main aim of the study is the enhancement of Light Alloy Drill Pipe material properties based on the results of the comprehensive studies of the aluminum alloy samples series, including its tribological tests on friction machines. The methods used in the research: study of light alloy drill pipe specimens wear in contact with the steel casing (45 D group) on the friction machine UMT 2168 and tester FANN in fluid medium-work-study of light alloy drill pipe specimens in contact «metal-rock» on the friction machine AI-3M in fluid medium-work-study of light alloy drill pipe specimens in «casing - drill pipe» system on the friction machine II-5018 in fluid medium. The results. The paper demonstrates that the methods based on machines UMT-2168, II-5018, AI-3M and tester FANN allow simulating friction process of drill pipe made of light alloy providing physical similarity of tribological process of «drill pipe - casing», «drill pipe - rock» pairs in various drilling fluids. The authors have studied the effect of the applied drilling fluids with lubricants and polymeric additives on performance of tribological drilling fluids properties in relation to the friction pair «metal-rock». It is recommended to apply the severe deformation technique, in particular the equal channel angular pressing, to obtain ultra-fine grain structure in aluminum alloys with the given physical and mechanical properties required to improve the tribotechnical features and increase of operating life of drill pipes.